DETERMINANTS OF CLIMATE RISK MANAGEMENT STRATEGIES AMONG RURAL COMMUNITIES IN EKITI STATE, NIGERIA - Famuyini, C. A.; Akinola, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
As part of the major effort to addressing climate risk in Nigeria, a study on climate risk management strategies has been carried out in Ekiti State, Nigeria. This study employed a multistage sampling techniques in selecting respondents from the population in the study area.Data were collected with a structured questionnaire.A total of 110 respondents were sampled for this study.The collected data were analysed using descriptive and inferential statistics (multinomial logit model). The analysis revealed that the average age of the farmers in the area is 46years and are relatively educated. The percentage of the farmers that used one or more of risk management strategies were 95%, while only 5% of the farmers do not use any in the area of study. The result of the multinomial logit regression revealed that household size, level of education, age of farmers, farm size and farming experience were the various factors that were significant determinants of the choice of various management strategies used. There is therefore the need to put in place a proactive policies and programs that will encourage farmers to be more educated by acquiring formal education and enhanced farming experience that will enable them to manage climate risk more effectively. This would go a long way in reducing the negative impact of climate on their productivity which will in turn improve their income and thus ensures a better livelihood.